An exploratory perspective on sustainable tourism as wise-use of a protected wetland in Thailand - Dhakal, Subas P. (Inderscience Enterprises Ltd, 2014)
The Ramsar Convention on Wetlands has for the first time formally recognised the role of tourism at the 2012 Conference of the Parties. This recognition is likely to catalyse sustainable tourism (ST) as wise-use of wetlands (WW) – balancing ecological and socio-economic priorities – in developing countries like Thailand. However, a comprehensive understanding of policy intricacies and community realities is necessary in order for the ST-WW nexus to materialise. This paper responds to this need and utilises a community-capitals framework to assess the challenges and opportunities associated with ST in a protected wetland on the outskirts of Bangkok.